Arrest campaign of the Ba’athists in Erbil Following the February 8, 1963 Coup: (A documentary Study) - Burhan Hatam Othman; Nihro Mohammed Abulqader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research, based on unpublished official Iraqi documents, has touched on the campaign of arrests carried out by the Baathist regime after the February 8, 1963 coup in the cities of Iraq and Kurdistan, including Erbil, in which the National Guard and other security and military agencies arrested hundreds of people from the city and regions. Administratively affiliated. The research sheds light on the issue of the arrest of members and supporters of the Iraqi Communist Party and the Kurdistan Democratic Party. Additionally, it details the detention and arrest of individuals from different classes and groups such as peasants, professionals, merchants, teachers, employees, children, women, and the elderly. This research also focuses on the prisons and detention centers where people from Erbil were held, their conditions including torture at the detention facilities. To sum up, data included in this research concerning the number of detainees from Erbil and its districts and sub-districts are based on the information gathered from the used documents.